Influence of surfactant on conductivity, capacitance and doping of electrodeposited polyaniline films - Kayishaer, Aihemaiti; Magnenet, Claire; Pavel, Ileana-Alexandra; Halima, Hamdi Ben; Moutarlier, Virginie; Lakard, Boris; Redon, Nathalie; Duc, Caroline; Lakard, Sophie (Frontiers in Materials, 2024)
The electrodeposition of polyaniline films is usually carried out in acid solutions such as hydrochloric acid, perchloric acid or sulfuric acid, and more rarely in organic acids such as camphorsulfonic acid (CSA). In this study, the impact of the presence of a surfactant in the electrolytic solution based on hydrochloric acid or CSA was evaluated by successively using anionic (sodium dodecyl sulfate, SDS), cationic (cetyltrimethylammonium bromide, CTAB), and non-ionic (Tritonx100) surfactants. Whatever the surfactant and the acid used, the electrochemical oxidation of aniline has successfully led to the formation of a thick polyaniline (PANI) film through a quasi-reversible reaction controlled by the diffusion of aniline monomers. The nature of the surfactant was shown to affect physico-chemical properties of the film, in particular its morphological features (morphology, thickness, roughness), electrochemical activity, specific capacitance, and conductivity. For example, PANI films containing SDS had a spongy morphology when PANI films containing Tritonx100 had a more fibrous and compact structure. Glow Discharge Optical Emission Spectroscopy (GDOES) experiments also highlighted differences depending on the acid used since chloride anions, from HCl, were present only on the top surface of the PANI films when camphorsulfonate anions were present everywhere throughout the polymer film, which impacts the doping process and electrochemical activity of the films. Moreover, the specific capacitance of the PANI/CSA films is higher and more sensitive to current density variation than the one of PANI/HCl films.Finally, electrochemical impedance experiments evidenced that the conductivity of PANI films electrodeposited from CSA solutions was much higher than the one of PANI films prepared from HCl solutions, and highly dependent on the nature of the surfactant, the most conductive films being obtained in the presence of SDS and Tritonx100. Therefore, the originality of this work comes from the possibility of modulating the conductivity, capacitance and electroactivity of electrodeposited polyaniline films using surfactants of different polarity, and from the determination of the distribution of ions in the films using the GDOES technique, which is rarely used to characterise organic films.